A Comparative Study of Sea Level Change in Maldives and Sri Lanka during the Holocene Period - Katupotha, K.N.J. (My University, 2015)
All the morphological features that comprise the continental shelf of the Maldives Islands and Sri Lanka share a geological history attributed the Quaternary period and reveal Pleistocene and Holocene sea level changes in both countries. The island chains of Maldives and on/near shore areas of the continental shelf of Sri Lanka are composed primarily of reef-derived carbonate sediments deposited during post-glacial and interglacial periods, in relation to sea level changes. However, research work carried out in Sri Lanka on sea level change is scanty compared to Maldives for an in-depth comparative study. This paper attempts to examine the similarity of the Holocene sea level changes in the Maldives and Sri Lanka based on the review of relevant published research papers, Radiocarbon isotopic radiometric dates and changes to past sea level curves.
Department of Geography, University of Sri Jayewardenepura, Nugegoda 10250, Sri Lanka e-mail: katupotha@sjp.ac.lk
Keywords: Holocene high sea levels; Islands and island chains; Maldives; Sri Lanka